Effect of tillage methods and nitrogen management practices on soil mineral nitrogen and grain protein, and yield of wheat (Triticum aestivum)in rice (Oryza sativa)-wheat system - S, SUDARSHAN; SHEKHAWAT, KAPILA; RATHORE, S S; M P, NIVEDITHA; SUPRIYA (The Indian Journal of Agricultural Sciences, 2024)
The field experiment was carried out during winter (rabi) season of 2020–21 at ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of tillage methods and nitrogen management practices on soil mineral nitrogen and grain protein and yield of wheat in rice- wheat system. The experiment was laid out in a split plot design (SPD), where the main plots included 4 different crop establishment methods, and the sub-plots tested 4 nitrogen management strategies that were replicated thrice. The results showed that, residue retention in zero tillage recorded significantly (P